The Legal Protection Towards Traditional Clothes: Intellectual Property Regimes in ASEAN - Ria Wierma Putri; Yunita Maya Putri; Mahathir Muhammad; Tristyanto Tristyanto (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2022)
Traditional clothing is one of the essential identities in Southeast Asian countries, knowns as ASEAN members; it was once used to showcase individual status in the community. It is still important today and worn on particular occasions to preserve tradition, and now it's emerged as one of the commercial goods. Yet, it becomes a vulnerable commodity when it becomes the object of cultural piracy, dispute of ownership, and disagreement of origin. The problem will continue to be detrimental to indigenous peoples who own it and possibly rift the relationship between ASEAN countries. The protection of traditional clothing in ASEAN is still weak, and there has been no specific legal instrument to regulate it. The intellectual property right (IPR) regime protects traditional clothing as a traditional cultural expression (TCE). TCE protection is part of the international regulation of intellectual property; however, without it well-implemented at the domestic level, TCE can easily be claimed as belonging to other parties who first published and registered them. This research will examine the legal protection of traditional clothes under IPR regimes in ASEAN in their national legal regulations. This research uses a comparative approach that primarily examines the laws and regulations governing the protection of Intellectual Property Rights in ASEAN countries. This research indicates that no single country in ASEAN has a specific law related to traditional cultural expressions (TCE) protection on traditional clothes. The protection for traditional clothes will be embedded in other IPR regimes such as Copyright, trademark, or non-IPR legislation.